2011
DOI: 10.1200/jco.2011.29.4_suppl.49
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of genetic aberrations in gastrointestinal stromal tumors.

Abstract: 49 Background: Gastrointestinal stromal tumours (GISTs) contain oncogenic KIT or PDGFRA tyrosine kinase (TK) mutations leading to disturbance of downstream signaling pathways that contribute to GIST pathogenesis. Additional genetic aberrations were found in GISTs, demonstrating the involvement of other genes important in tumor progression. The aim of the study was to evaluate the prognostic relevance of different TK mutations in GISTs and to analyze the additional genetic aberrations in GISTs according to mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Tumor size, origin and mitotic activity are the leading features that have been widely approved as being predictive of clinical outcome for resected GIST patients (Dematteo et al, 2008). The discovery of the particular molecular abnormalities and mutational analyses provided to define certain GIST subtypes that demonstrate divergent responses to TKI therapy and had different clinical behavior (Mazurenko et al, 2011). Previous studies demonstrated that KIT exon 11 mutations show the greatest benefit from imatinib treatment, while the patients with exon 9 mutations require a higher imatinib dosage to reach a higher response and are associated with a worse course than the patients with exon 11 mutations (Singer et al, 2002;Debiec-Rychter et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor size, origin and mitotic activity are the leading features that have been widely approved as being predictive of clinical outcome for resected GIST patients (Dematteo et al, 2008). The discovery of the particular molecular abnormalities and mutational analyses provided to define certain GIST subtypes that demonstrate divergent responses to TKI therapy and had different clinical behavior (Mazurenko et al, 2011). Previous studies demonstrated that KIT exon 11 mutations show the greatest benefit from imatinib treatment, while the patients with exon 9 mutations require a higher imatinib dosage to reach a higher response and are associated with a worse course than the patients with exon 11 mutations (Singer et al, 2002;Debiec-Rychter et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with KIT mutations, point mutations and duplication in KIT axon 11 had better survival than GIST with other KIT mutations [111]. …”
Section: Introductionmentioning
confidence: 99%